2016
DOI: 10.5812/nmsjournal.28717
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Work Ability Among Emergency Nurses in Isfahan, Iran

Abstract: Background: Job stress is one of the most common health problems with clinical and psychological consequences, which can affect work ability among emergency nurses. Nevertheless, more studies are needed to shed light on the status of this disorder and its relevance to work ability in nurses in the emergency departments (EDs). Objectives: The current study aimed to determine job stress among emergency nurses and its association with work ability. Methods: This cross-sectional study was conducted in 2013 in hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…61,63,64 This can be explained by the fact that younger ICU physicians are more prone to professional burnout. 65 Divorced participants had high levels of total and patient-related professional burnout levels, which is also similar to other studies in the literature. 60,63…”
Section: Discussionsupporting
confidence: 88%
“…61,63,64 This can be explained by the fact that younger ICU physicians are more prone to professional burnout. 65 Divorced participants had high levels of total and patient-related professional burnout levels, which is also similar to other studies in the literature. 60,63…”
Section: Discussionsupporting
confidence: 88%
“…In the recent literature, the prevalence of psychological distress among nurses reported to be high. The stress prevalence has been reported to be as high as 55% (Nasr-Esfahani, Masoumi, Mohamadirizi, & Mohamadirizi, 2017), the prevalence of anxiety as 41.1% (Zhou et al, 2018) and the prevalence of depression as 69.4% (Ali, Rasheed, Naz, & Siddiqui, 2018). Furthermore, in a recent national study conducted on 1,790 nurses in USA, they found that the prevalence of stress, anxiety and depression (SAD) were 38.7%, 51.97% and 32.8% (Melnyk et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However, Hashemian et al (2015) reported that nurses who work night and rotation shifts had lower levels of stress. A shortage of nursing staff was identified as the most common cause of job stress among nurses (Nasr-Esfahani et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a nurse is a means of communication between physicians and patients [ 18 ]. The nurse faces a high risk for occupational fatigue, work-related occupational stress, and sleep problems [ 19 22 ], those factors affected the nurse’s level of work ability [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%